Konsistensi Pemikiran dan Gerakkan Dakwah Organisasi Mathla’ul Anwar di Indonesia - Fatimatuzahrotul Aini (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
This article discusses the consistency of thought and movement for the Da'wah of the Mathla'ul Anwar organization in Indonesia. Mathla'ul Anwar (MA) as one of the largest Islamic community organizations (ormas) in Indonesia after Nahdlatul Ulama and Muhammadiyah at the time of Indonesian independence with the Islamic modernization movement to foster a spirit of struggle among the people so as not to be affected by the exploitation of the imperialists, especially the Banten area. . MA organizations to date maintain the complete guidelines of MA organizations, namely focusing on da'wah, education and social activities. The MA combines the madrasa system with the pesantren system, where this system aims to produce professional preachers who have broad insight and have good morals. The MA until now has the organizational goal of prioritizing amar ma'ruf nahi munkar by developing the institution of Mubaligh Mathla'ul Anwar which contains young da'I cadres. The consistency of Khittah Mathla'ul Anwar as a neutral Islamic community organization does not follow any political issues, even though during the New Order era it had lost the consistency of its organizational foundations. The Supreme Court participated in developing young Indonesian da'I cadres and carried out the activities of the Wattabligh fatwa assembly. The author uses an approach with a literature review method and processing descriptive data. This paper is based on the idea of ​​consistent MA in the basic lines of becoming a mass organization and da'wah movement in society.